1997
DOI: 10.1002/(sici)1097-0215(19970807)72:4<599::aid-ijc8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity at theTP53 gene: Independent occurrence from genetic instability events in node-negative breast cancer

Abstract: TP53 abnormalities have been reported as an early event in the process of cellular transformation of human breast cancers, and involved in mammary-tumor evolution, from in situ to invasive disease. In this study, node-negative (N 2 ) tumors were examined for TP53 allelic loss in relation to different genetic instability events, including allelic loss at chromosome 17p13.3 and c-H-ras-1 loci, as well as alteration of the c-myc and c-erbB-2/neu oncogenes. TP53 allelic loss was analyzed to determine whether such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…In the present study, using the same probe as Xing et al (1996) we observed high levels of amplification at a lower frequency. The 9% incidence of c‐ erb B‐2 amplification that we observed in the control series featuring older patients with node‐negative breast cancers is similar to the 9 to 10% rate reported in 2 large series of patients from Australia and France (Seshadri et al, 1996; Lizard‐Nacol et al, 1997). The relatively high frequency of c‐ erb B‐2 amplification (38 to 68%) in breast cancer in young women reported by Xing et al (1996) is equal to or greater than the 18 to 39% range of c‐ erb B‐2‐gene amplification or p185erbB2‐protein over‐expression reported for non‐EOBC (review by Ross and Fletcher, 1998; Press et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, using the same probe as Xing et al (1996) we observed high levels of amplification at a lower frequency. The 9% incidence of c‐ erb B‐2 amplification that we observed in the control series featuring older patients with node‐negative breast cancers is similar to the 9 to 10% rate reported in 2 large series of patients from Australia and France (Seshadri et al, 1996; Lizard‐Nacol et al, 1997). The relatively high frequency of c‐ erb B‐2 amplification (38 to 68%) in breast cancer in young women reported by Xing et al (1996) is equal to or greater than the 18 to 39% range of c‐ erb B‐2‐gene amplification or p185erbB2‐protein over‐expression reported for non‐EOBC (review by Ross and Fletcher, 1998; Press et al, 1997).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, using the same probe as Xing et al (1996) we observed high levels of amplification at a lower frequency. The 9% incidence of c-erbB-2 amplification that we observed in the control series featuring older patients with node-negative breast cancers is similar to the 9 to 10% rate reported in 2 large series of patients from Australia and France (Seshadri et al, 1996;Lizard-Nacol et al, 1997). The relatively high frequency of c-erbB-2 amplification (38 to 68%) in breast cancer in young women reported by Xing et al (1996) is equal to or greater than the 18 to 39% range of c-erbB-2-gene amplification or p185erbB2protein over-expression reported for non-EOBC (review by Ross and Fletcher, 1998;Press et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Mutations and deletions of the p53 gene are relatively common in mammary carcinomas 2 and appear to occur early in carcinogenesis. 3 Most of them result in abrogation of the growth inhibitory or apoptotic potential of the encoded protein and thus facilitate unrestrained proliferation and progressive genomic instability (reviewed in refs 4 and 5). HER-2/neu, the gene coding for c-erbB-2, a tyrosine kinase receptor sharing sequence homologies with the epidermal growth factor receptor (EGFR), 6 is frequently amplified in ductal carcinomas of the breast, 7,8 which appears to be associated with a more aggressive behaviour of the tumours.…”
Section: Introductionmentioning
confidence: 99%